Efficient and Secure Routing Protocol Based on Encryption and Authentication for Wireless Sensor Networks - Jiliang Zhou (International Journal of Distributed Sensor Networks)
One concerned issue in the routing protocol for wireless sensor networks (WSNs) is how to provide with as much security to some special applications as possible. Another is how to make full use of the severely limited resource presented by WSNs. The existing routing protocols in the recent literatures focus either only on addressing security issues while expending much power or only on improving lifetime of network. None of them efficiently combine the above-mentioned two challenges to one integrated solutions. In this paper, we propose efficient and secure routing protocol based on encryption and authentication for WSNs: BEARP, which consists of three phases: neighbor discovery phase, routing discovery phase, and routing maintenance phase. BEARP encrypts all communication packets and authenticates the source nodes and the base station (BS), and it ensures the four security features including routing information confidentiality, authentication, integrity, and freshness. Furthermore, we still design routing path selection system, intrusion detection system, and the multiple-threaded process mechanism for BEARP. Thus, all the secure mechanisms are united together to effectively resist some typical attacks including selective forwarding attack, wormhole attacks, sinkhole attacks, and even a node captured. Our BEARP especially mitigates the loads of sensor nodes by transferring routing related tasks to BS, which not only maintains network wide energy equivalence and prolongs network lifetime but also improves our security mechanism performed uniquely by the secure BS. Simulation results show a favorable increase in performance for BEARP when compared with directed diffusion protocol and secure directed diffusion protocol in the presence of compromised nodes.